Contribution of storytelling for the creation of emotional marketing in a company of purified water of bahía de Caráquez, Ecuador 2019 - César Arturo Carbache Mora (2019)
Currently, brands have realized that creating an emotional bond in their target groups opening advantages over competition and have found in the old art of storytelling the perfect ally for that purpose. Storytelling is a powerful strategy that allows you to create that emotional link between producer and consumer. The objective of this research is to analyze the contribution of storytelling to generate emotional marketing strategies in purified water companies in the city of Bahía de Caráquez. The methodology implemented was the observation and application of surveys to customers of said product. The results were that consumers by brand preference are at 26.7 percent. However, 21.7 percent have little knowledge of the advertising of the companies under study. It is proposed that companies engaged in this commercial activity lack emotional marketing strategies based on the creation of stories that expand their field of service, attraction and customer loyalty.